İYONKÜRE KRİTİK FREKANSININ (FOF2) ENLEM İLE DEĞİŞİMİNİN İNCELENMESİ - ALAN, ŞAHSENEM (Fırat Üniveristesi, 2013)
Bu çalışmada, 10 Ekim 1978 tarihindeki, Kashima yer istasyonundan 90?K ile 90?G enlemleri ve 30, 35, 40, 45 derece Doğu boylamları için oluşturulan haritalar kullanılarak elde edilen iyonkürenin F2-bölgesinin kritik frekansının (foF2) günlük değişimleri incelenmiştir. Elde edilen sonuçlarda kritik frekansın (foF2) 06.00 ile 07.00 saatlerinde artarken saat 15.00 ile saat 17.00 saatlerde azaldığı görülmüştür. Elektron yoğunluğunun enlemle dağılımında gözlenen dip ekvatoru üzerindeki çukurlar ile birlikte +20 ile -20 enlemleri arasındaki tepeler, kritik frekansın enlemle dağılımında saat 20.00?da meydana geldiği gözlenmiştir. Kritik frekansın enlemsel-boylamsal dağılımının karakteristik olarak elektron yoğunluğunun 06.00 ile 17.00 saatlerindeki enlemsel-boylamsal dağılımına eşlik ettiği görülmüştür.

In this study, the daily variations of the critical frequency (foF2) of the F2-layer of the ionosphere obtained from the Kashima station on 10 October 1978 are investigated for 90?N and 90?S latitudes and 30?, 35?, 40?, 45?E longitudes by using generated maps. It is observed that the values of the critical frequency increases at 06.00-07.00 hours and decrease gradually at 15.00-17.00 hours. The troughs in the dip equator and the crests between +20 and -20 latitudes occurred in the latitudinal variations of the electron density distributions are also appeared in the latitudinal variations of the critical frequency at 20.00 hours. The latitudinal-longitudinal distribution of the critical frequency characteristically corresponds to the latitudinal-longitudinal distribution of the electron density at 06.00-17.00.
Investigation of the variation of the ionospheric critical frequency (foF2) with latitude
Keywords: Fizik ve Fizik Mühendisliği